Application of a BRAF V600E mutation-specific antibody for the diagnosis of hairy cell leukemia - Andrulis, Mindaugas; Penzel, Roland; Weichert, Wilko; Deimling, Andreas von; Capper, David (The American journal of surgical pathology, 2012)
In recent times BRAF V600E mutations have emerged as a genetic hallmark of hairy cell leukemia (HCL). This specific point mutation is present in virtually all cases of HCL but is exceedingly rare in other peripheral B-cell neoplasms. In this study we investigated the application of a BRAF V600E mutation-specific antibody (clone VE1) to differentiate HCL from HCL mimics, such as HCL variant and splenic marginal zone lymphoma. A total of 52 routinely processed formalin-fixed paraffin-embedded tissue specimens were investigated (bone marrow, n=46; spleen, n=6) for expression of V600E-mutated BRAF protein. All 32 cases of HCL were scored positive, and all non-HCL cases were scored negative. In 28 of 30 HCL cases the presence of a BRAF V600E mutation could be confirmed by direct sequencing, whereas no BRAF mutations were detected among 20 HCL mimics. We further screened 228 mature B-cell neoplasms with VE1 and detected 1 positive case of chronic lymphocytic leukemia. Sequencing confirmed the presence of a BRAF V600E mutation. In conclusion, we demonstrate that VE1 immunohistochemistry can be used to reliably differentiate HCL from HCL-mimicking entities. This on-slide technique might be particularly helpful in interpreting challenging biopsies with low tumor content.